A Rapidly-Incremented Tethered-Swimming Test for Defining Domain-Specific Training Zones - Pessôa Filho, Dalton M. [UNESP]; Siqueira, Leandro O.C. [UNESP]; Simionato, Astor R. [UNESP]; Espada, Mário A.C.; Pestana, Daniel S.; DiMenna, Fred J. (De Gruyter, 2017)
The purpose of this study was to investigate whether a tethered-swimming incremental test comprising small increases in resistive force applied every 60 seconds could delineate the isocapnic region during rapidly-incremented exercise. Sixteen competitive swimmers (male, n = 11; female, n = 5) performed: (a) a test to determine highest force during 30 seconds of all-out tethered swimming (Favg) and the ΔF, which represented the difference between Favg and the force required to maintain body alignment (Fbase), and (b) an incremental test beginning with 60 seconds of tethered swimming against a load that exceeded Fbase by 30% of ΔF followed by increments of 5% of ΔF every 60 seconds. This incremental test was continued until the limit of tolerance with pulmonary gas exchange (rates of oxygen uptake and carbon dioxide production) and ventilatory (rate of minute ventilation) data collected breath by breath. These data were subsequently analyzed to determine whether two breakpoints defining the isocapnic region (i.e., gas exchange threshold and respiratory compensation point) were present. We also determined the peak rate of O2 uptake and exercise economy during the incremental test. The gas exchange threshold and respiratory compensation point were observed for each test such that the associated metabolic rates, which bound the heavy-intensity domain during constant-work-rate exercise, could be determined. Significant correlations (Spearman's) were observed for exercise economy along with (a) peak rate of oxygen uptake (ρ = .562; p < 0.025), and (b) metabolic rate at gas exchange threshold (ρ = -.759; p < 0.005). A rapidly-incremented tethered-swimming test allows for determination of the metabolic rates that define zones for domain-specific constant-work-rate training.
Keywords: constant-work-rate exercise; exercise economy; gas exchange threshold; heavy intensity; isocapnic region; respiratory compensation point